Rigosertib in combination with azacitidine in patients with myelodysplastic syndromes or acute myeloid leukemia: Results of a phase 1 study. (July 2020) - Navada, Shyamala C.; Garcia-Manero, Guillermo; OdchimarReissig, Rosalie; Pemmaraju, Naveen; Alvarado, Yesid; Ohanian, Maro N.; John, Rosmy B.; Demakos, Erin P.; Zbyszewski, Patrick S.; Maniar, Manoj; Woodman, Richard C.; Fruchtman, Steven M.; et al.
Highlights: No dose-limiting toxicity was observed with oral rigosertib + standard azacitidine. The safety profile was similar to standard dose single-agent azacitidine. Overall response rates were 56% (overall), 78% (MDS/CMML) and 29% (AML). Abstract: Phase 1 results from a Phase 1/2 study comprise 18 patients with myelodysplastic syndromes (MDS; n = 9), acute myeloid leukemia (AML; n = 8), and chronic myelomonocytic leukemia (CMML; n = 1) who were either hypomethylating agent naïve ( n = 10) or relapsed/refractory following prior hypomethylating agent therapy ( n = 8) (NCT01926587). Patients received oral rigosertib, an inhibitor of Ras-effector pathways, in 3 successive cohorts (140 mg twice daily, 280 mg twice daily, or 840 mg/day [560 mg morning/280 mg evening]) for 3 weeks of a 4-week cycle. Patients received parenteral azacitidine (75 mg/m 2 /day × 7 days) during the second week; the cycle repeated every 4 weeks. The combination was well tolerated for a median of 4 (range 1–41) cycles, with 72% of patients experiencing ≥1 serious adverse events. No dose-limiting toxicities were observed. Thus, no maximum tolerated dose was reached. The most frequently reported adverse events were diarrhea (50%), constipation, fatigue, and nausea (each 44%), and pneumonia and back pain (each 33%). Sequential administration demonstrated an overall response rate of 56% in evaluable patients, with responses observed in 7/9 MDS/CMML patients (78%) and 2/7 AML patients (29%). Further clinical studies are warranted to investigate this doublet therapy in patients with myeloid malignancies.